Some results on order bounded almost weak Dunford-Pettis operators - Machrafi, N.; Elbour, A.; Moussa, M. (Methods of Functional Analysis and Topology, 2016)
We give some new characterizations of almost weak Dunford-Pettis operators and we investigate their relationship with weak Dunford-Pettis operators.